1997
DOI: 10.1002/(sici)1099-1263(199701)17:1<75::aid-jat397>3.3.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Ifosfamide Metabolite Chloroacetaldehyde Causes Renal Dysfunction in vivo

Abstract: Renal injury is a common side-effect of the chemotherapeutic agent ifosfamide. Current evidence suggests that the ifosfamide metabolite chloroacetaldehyde may be responsible for this nephrotoxicity. The present study examined the effect of increasing amounts of intrarenally infused chloroacetaldehyde on kidney function, glutathione content and malondialdehyde formation. The ability of the uroprotectant medication sodium 2-mercaptoethanesulfonate (mesna) to prevent chloroacetaldehyde-induced renal injury was al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
41
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 0 publications
4
41
0
Order By: Relevance
“…It has been shown that only metabolites of IFO are toxic to the kidney, whereas the prodrug is not (10). IFO must be oxidized by cytochrome 3A5 (CYP3A5) and CYP2B6 oxidase to acquire an antineoplastic activity (11,12).…”
Section: Introductionsupporting
confidence: 90%
“…It has been shown that only metabolites of IFO are toxic to the kidney, whereas the prodrug is not (10). IFO must be oxidized by cytochrome 3A5 (CYP3A5) and CYP2B6 oxidase to acquire an antineoplastic activity (11,12).…”
Section: Introductionsupporting
confidence: 90%
“…Both acrolein and chloroacetaldehyde cause toxicity in LLC-PK1 cells (Mohrmann et al, 1992(Mohrmann et al, , 1993; however, acrolein does not impair the function of isolated perfused rat kidneys or after long-term exposure in animal models (Parent et al, 1992;Zamlauski-Tucker et al, 1994). Chloroacetaldehyde has consistently shown a concentration-dependent cytotoxic effect in several in vitro models (i.e., porcine or rabbit cultured renal tubules and isolated perfused rat kidneys) with a minimum toxic concentration that ranges from 12.5 to 64 M (Mohrmann et al, 1993;Springate, 1997;Springate et al, 1999). In cultured primary human proximal tubules cells, the minimum chloroacetaldehyde concentration for toxicity was reported to be 500 M, which is well above the observed peak plasma concentrations (i.e., 0.5-109 M) in patients receiving standard doses of ifosfamide (Goren et al, 1986;Kurowski and Wagner, 1993;Dubourg et al, 2001).…”
mentioning
confidence: 67%
“…IF mustard, which is produced by ring hydroxylation pathway, is the pharmacological active metabolite, whereas chloroacetaldehyde, which is produced from chlorethyl side oxidation, is largely believed to be responsible for the nephrotoxic effects of IF. 9 Many recent studies considered statins as the potential therapeutic agent for a targeted conservative treatment of female gonadal function, fertility 10 endometriosis in humans 11 and reduced mortality among women affected by endometrial/ovarian malignancies. 12 Whereas Andrisani et al 13 found Astaxanthin (Asta), a photo-protective red pigment of the carotenoid family, utilized to decrease male idiopathic infertility.…”
Section: Introductionmentioning
confidence: 99%